High fidelity: extra‐pair fertilisations in eight Charadrius plover species are not associated with parental relatedness or social mating system. (8th June 2017) - Maher, Kathryn H.; Eberhart‐Phillips, Luke J.; Kosztolányi, András; Remedios, Natalie dos; Carmona‐Isunza, María Cristina; Cruz‐López, Medardo; Zefania, Sama; St Clair, James J. H.; Alrashidi, Monif; Weston, Michael A.; Serrano‐Meneses, Martín A.; Krüger, Oliver; et al.
Abstract : Extra‐pair paternity is a common reproductive strategy in many bird species. However, it remains unclear why extra‐pair paternity occurs and why it varies among species and populations. Plovers ( Charadrius spp.) exhibit considerable variation in reproductive behaviour and ecology, making them excellent models to investigate the evolution of social and genetic mating systems. We investigated inter‐ and intra‐specific patterns of extra‐pair parentage and evaluated three major hypotheses explaining extra‐pair paternity using a comparative approach based on the microsatellite genotypes of 2049 individuals from 510 plover families sampled from twelve populations that constituted eight species. Extra‐pair paternity rates were very low (0 to 4.1% of chicks per population). No evidence was found in support of the sexual conflict or genetic compatibility hypotheses, and there was no seasonal pattern of extra‐pair paternity (EPP). The low prevalence of EPP is consistent with a number of alternative hypotheses, including the parental investment hypothesis, which suggests that high contribution to care by males restricts female plovers from engaging in extra‐pair copulations. Further studies are needed to critically test the importance of this hypothesis for mate choice in plovers.